From social peace to code of silence: The social ethics of sutura in Senegal - Falcão, R. (Cadernos de Estudos Africanos, 2023)
Normally translated as discretion, sutura is an important local value in Senegal. Its protective regime starts with the idea that being discreet has an inherent social value. In its ideal dimension it is said to be a warranty for social peace. Its rather pragmatic consequences, on the other hand, are felt on communication, generating uncertainty and ambiguity; on the social construction of gender, highlighting that protection is unequally distributed; and on the political sphere, where certain subjects, perceived as private, struggle to be represented. Sutura is here described through several complementary and contradictory interpretations. At the same time, as a defensive mode of communication and an ethics of privacy, but also, paradoxically, as a dark cover or a code of silence, protecting the shortcomings of Senegalese patriarchal cultures. ************************************************************************************************************************** Normalmente traduzida por discrição, a sutura é um valor local importante no Senegal. O seu regime de proteção parte da ideia de que ser discreto tem um valor social inerente. Na sua dimensão ideal, diz-se que é uma garantia de paz social. As suas consequências bastante pragmáticas, por outro lado, fazem-se sentir na comunicação, gerando incerteza e ambiguidade; na construção social do género, evidenciando que a proteção é distribuída de forma desigual; e na esfera política, onde certos assuntos, vistos como privados, lutam para serem representados. A sutura é aqui descrita através de várias interpretações complementares e contraditórias: ao mesmo tempo, como um modo de comunicação defensivo e uma ética da privacidade, mas também, paradoxalmente, como um disfarce obscuro ou um código de silêncio, que protege as lacunas das culturas patriarcais senegalesas.